Margin Analysis Of Trade Administration And Marketing Strategy Of Fish Catch Using Cantrang At Ppp Klidang Lor, Batang Central Java - Kusuma Dewi Ratnasari, Intan; Wijayanto, Dian; Boesono, Herry (Green Publisher Indonesia, 2022)
PPP Klidang Lor Batang is one of the fishing ports still dominated by cantrang fishing gear. The purpose of this study was to analyze the margins of trading and marketing strategies by the waiters who use cantrang. This study used a descriptive method with data collection by observing directly in the field at PPP Klidang Lor. The population used in taking respondents in this study were fishermen who used cantrang fishing gear. Data analysis was carried out using qualitative analysis and quantitative analysis. The catch and variety is one of the factors for the high and low income of fishermen. The catch that is traded to TPI, middlemen, retailers, or even consumers without a good trading strategy will not maximize the income earned by fishermen. By analyzing the trading system margins of fishermen, TPI, middlemen, retailers, and consumers, alternative strategies for fishermen will be known in order to increase marketing of the catch they get. The purpose of this study is to determine the margin of trade and the composition of catches, marketing channels. Analysis of the data used to determine the value of the margin of trade using BEP, HPP, R/C, Fisherman's share. Meanwhile, the marketing strategy uses SWOT analysis to determine the internal and external factors of marketing the fisherman's catch using cantrang fishing gear.